2010
DOI: 10.5042/jap.2010.0293
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between learning and practice: from where we were to where we are now

Abstract: Users who downloaded this article also downloaded: (2013),"Safeguarding vulnerable adults: exploring the challenges to best practice across multi-agency settings", The Journal of Adult Protection, Vol. 15 Iss 2 pp. 85-95 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…It is reasonable to work on an assumption that if behaviour is reflective of individual boundary attitude it will be amenable to interventions that are directed towards amending it -after all, this is an assumption that permeates the world of attitude-behaviour connections (Glasman and Albarracín, 2006), as well as the world of staff development in adult safeguarding more generally (Pike et al, 2010). However, on the basis of this evidence, the findings provoke critical reflection on how professional and personal boundaries are currently established and regulated within the care sector.…”
Section: Resultsmentioning
confidence: 99%
“…It is reasonable to work on an assumption that if behaviour is reflective of individual boundary attitude it will be amenable to interventions that are directed towards amending it -after all, this is an assumption that permeates the world of attitude-behaviour connections (Glasman and Albarracín, 2006), as well as the world of staff development in adult safeguarding more generally (Pike et al, 2010). However, on the basis of this evidence, the findings provoke critical reflection on how professional and personal boundaries are currently established and regulated within the care sector.…”
Section: Resultsmentioning
confidence: 99%
“…These studies scored between 19–36 on the Hawker et al (2002) indicating generally good quality. We included three case studies: Phair & Manthorpe, 2012; Lee‐Foster, 2010; and Pike, Indge, Leverton, Ford, & Gilbert, 2010. Case studies may be less rigorous in their methods because researchers are evaluating their own work or because the focus of the study is necessarily local and small.…”
Section: Resultsmentioning
confidence: 99%
“…In several papers, the findings reflected a range of training types, in which training might have happened recently (Lee‐Foster, 2010; Schofield et al, 2012; Willner et al, 2011, 2013) or up to 2 years previously (McCormick et al, 2017; Morriss et al, 2017; Phair & Manthorpe, 2012; Sawhney et al, 2009), in which case participants may have attended more than one training intervention. In three cases, MCA training was combined with training in related issues (communication (Lee‐Foster, 2010), record‐keeping (Willner et al, 2013), safeguarding and human rights (Pike et al, 2010)). Responses are varied and poorly reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Scotland, Adult Protection Committees, whose functions are similar to LSABs in England and Wales, have been disseminating SCRs and inquiry outcomes for learning and improvement (Cornish and Preston-Shoot, 2013). While evaluation of the impact of adult protection training has been limited (Campbell and Chamberlin, 2012) and it is by no means the case that training interventions inevitably lead to improvements in practice (Pike et al 2010), educational sessions have been found to be more effective than printed material in increasing people's knowledge and case management skills (Richardson et al, 2002). Where these can include case material such as that drawn from consolidated findings of SCRs the potential for impact is arguably stronger.…”
Section: Discussionmentioning
confidence: 99%